Cryptic aberrations may allow more accurate prognostic classification of patients with myelodysplastic syndromes and clonal evolution. Issue 7 (25th March 2020) - Svobodova, Karla; Lhotska, Halka; Hodanova, Lucie; Pavlistova, Lenka; Vesela, Denisa; Belickova, Monika; Vesela, Jitka; Brezinova, Jana; Sarova, Iveta; Izakova, Silvia; Lizcova, Libuse; Siskova, Magda; et al.
Abstract: The karyotype of bone‐marrow cells at the time of diagnosis is one of the most important prognostic factors in patients with myelodysplastic syndromes (MDS). In some cases, the acquisition of additional genetic aberrations (clonal evolution [CE]) associated with clinical progression may occur during the disease. We analyzed a cohort of 469 MDS patients using a combination of molecular cytogenomic methods to identify cryptic aberrations and to assess their potential role in CE. We confirmed CE in 36 (8%) patients. The analysis of bone‐marrow samples with a combination of cytogenomic methods at diagnosis and after CE identified 214 chromosomal aberrations. The early genetic changes in the diagnostic samples were frequently MDS specific (17 MDS‐specific/57 early changes). Most progression‐related aberrations identified after CE were not MDS specific (131 non‐MDS‐specific/155 progression‐related changes). Copy number neutral loss of heterozygosity (CN‐LOH) was detected in 19% of patients. MDS‐specific CN‐LOH (4q, 17p) was identified in three patients, and probably pathogenic homozygous mutations were found in TET2 (4q24) and TP53 (17p13.1) genes. We observed a statistically significant difference in overall survival (OS) between the groups of patients divided according to their diagnostic cytogenomic findings, with worse OS in the group with complex karyotypes ( P = .021). A combination of cytogenomic methods allowed us to detect many cryptic genomic changes and identify genes and genomic regions that may represent therapeutic targets in patients with progressive MDS.